DEVELOPMENT OF CORN STARCH BIODEGRADABLE FILMS REINFORCED BY NANOCELLULOSE FOR FOOD PACKAGING (Nativa, 2024)
ABSTRACT: The present paper evaluates the mechanical and physical characteristics of edible films made from corn starch (Zea mays L.) reinforced with nanocellulose. To do this, films were made with 0.4 and 0.08% cotton nanocellulose (NC) with plasticizer (0.4 and 1%). The mixture was emulsified between 1 and 3 min and dried for 20 h (36 and 50 °C). NC was obtained by acid hydrolysis for 6 days at 25 °C with 50% sulfuric acid and dialyzed to neutral pH. Cotton NC and NC-included film were analyzed using Fourier transform infrared spectroscopy. About the physical characteristics, it will be observed that there was no significant difference between the inclusion percentages. Accordingly, a 5% inclusion would be sufficient for smooth, transparent, flexible, non-cracked and homogeneous films. It is determined that the higher the percentage of NC, the lower the elasticity values, improving the films' hardness and transparency. Given that the percentage present in the NC test solution is 1.6%, its inclusion would be 0.4% (25 ml NC) and 0.08% (5 ml NC), indicating its great influence on films.Keywords: biodegradable fimls; starch; mechanical properties. Desenvolvimento de filmes biodegradáveis de amido de milho reforçados com nanocelulose para embalagens de alimentos RESUMO: No presente trabalho são avaliadas as características mecânicas e físicas de filmes comestíveis elaborados a partir de amido de milho (Zea mays L.) reforçados com nanocelulose. Para isso foram confeccionados filmes com 0,4 e 0,08% de nanocelulose de algodão (NC) com plastificante (0,4 e 1%): A mistura foi emulsionada entre 1 e 3 min e seca por 20 h (36 e 50 °C). A NC foi obtida por hidrólise ácida durante 6 dias a 25 °C com ácido sulfúrico a 50% e dialisada até pH neutro. Algodão NC e filmes incluídos em NC foram analisados por espectroscopia de infravermelho com transformada de Fourier. Em relação às características físicas, observar-se-á que não houve diferença significativa entre os percentuais de inclusão. Assim, uma inclusão de 5% seria suficiente para obter filmes lisos, transparentes, flexíveis, não fissurados e homogêneos. Determina-se que quanto maior o percentual de NC, os valores de elasticidade diminuem, melhorando a dureza e a transparência dos filmes. Dado que a percentagem presente na solução teste NC é de 1,6%, a sua inclusão seria de 0,4% (25 ml NC) e 0,08% (5 ml NC), o que indica a grande influência que tem nos filmes.Palavras-chave: filmes biodegradáveis; amido; propriedades mecânicas.